2020
DOI: 10.1186/s12879-020-05579-2
|View full text |Cite
|
Sign up to set email alerts
|

Treating HIV-associated cytomegalovirus retinitis with oral valganciclovir and intra-ocular ganciclovir by primary HIV clinicians in southern Myanmar: a retrospective analysis of routinely collected data

Abstract: Background Cytomegalovirus retinitis (CMVR) is an opportunistic infection in HIV-infected people. Intraocular or intravenous ganciclovir was gold standard for treatment; however, oral valganciclovir replaced this in high-income countries. Low- and middle-income countries (LMIC) frequently use intraocular injection of ganciclovir (IOG) alone because of cost. Methods Retrospective review of all HIV-positive patients with CMVR from February 2013 to April 2017 at a Médecins Sans Frontièrs HIV clinic in Myanmar. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
11
0
2
Order By: Relevance
“…Our patients did not deteriorate, and thus maintained a stable vision after treatment. Our results were similar to a study by Murray et al ,[ 13 ] which showed that nearly 60% of eyes treated on oral valganciclovir maintained a stable vision. Lack of improvement in vision in our patients could be attributed to mainly zone 1 involvement in the affected eyes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our patients did not deteriorate, and thus maintained a stable vision after treatment. Our results were similar to a study by Murray et al ,[ 13 ] which showed that nearly 60% of eyes treated on oral valganciclovir maintained a stable vision. Lack of improvement in vision in our patients could be attributed to mainly zone 1 involvement in the affected eyes.…”
Section: Discussionsupporting
confidence: 92%
“…In developed countries, where oral valganciclovir is the mainstay of therapy, intraocular injections of ganciclovir are the mainstay of therapy in developing countries. Table 2 compares the results from various studies treating CMVR,[ 10 11 13 14 15 16 17 ] with present study.…”
Section: Discussionmentioning
confidence: 92%
“…34 Recently, the group from Myanmar was the first to report the use of oral valganciclovir by HIV clinicians for treating CMVR in a developing country, and concluded with the finding that oral valganciclovir was safe and effective. 35 To our knowledge, there has been no effort to train HIV clinicians to screen for CMVR in SA. Currently, there is also no consensus regarding screening by ophthalmologists, particularly in the ART era.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the cost barrier, only ganciclovir was in use in developing countries in the past. However, valganciclovir is now started to be introduced in low and middle-income countries as it is available at a reduced price within the WHO essential medicines list [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%